Rasionalisasi Religius dalam Diskursus Keagamaan di Indonesia: Kasus Parmalim Batak Toba - Irwasyah Harahap (Antropologi Indonesia, 2000)
The Toba Batak, the followers of Parmalim (a local religion), have tried their best to preserve this local religion throughout the long oppression years by the Dutch and Christian missionary. The Parmalim practitioners did this up to recent times, in the midst of current ideas and assumptions about the civil-state religion based on 'monotheistic' belief. In this article, the author discusses the use of the concept 'religious rationalization' to refer to what the Parmalim followers have done in reconstructing their beliefs and religious practices. The author first examines the concept of 'religious rationalization' among anthropologists. He examines further the recent phenomenon of the civil-state religion, the Indonesian government's policies, its implications on the socio-religious-political situation among the Toba Batak, in particular among the Parmalim community, and the various existing interpretations.